Entrustability Scales: Outlining Their Usefulness for Competency-Based Clinical Assessment. (February 2016) - Rekman, Janelle; Gofton, Wade; Dudek, Nancy; Gofton, Tyson; Hamstra, Stanley J.
Abstract : Meaningful residency education occurs at the bedside, along with opportunities for situated in-training assessment. A necessary component of workplace-based assessment (WBA) is the clinical supervisor, whose subjective judgments of residents' performance can yield rich and nuanced ratings but may also occasionally reflect bias. How to improve the validity of WBA instruments while simultaneously capturing meaningful subjective judgment is currently not clear. This Perspective outlines how "entrustability scales" may help bridge the gap between the assessment judgments of clinical supervisors and WBA instruments. Entrustment-based assessment evaluates trainees against what they will actually do when independent; thus, "entrustability scales"—defined as behaviorally anchored ordinal scales based on progression to competence—reflect a judgment that has clinical meaning for assessors. Rather than asking raters to assess trainees against abstract scales, entrustability scales provide raters with an assessment measure structured around the way evaluators already make day-to-day clinical entrustment decisions, which results in increased reliability. Entrustability scales help raters make assessments based on narrative descriptors that reflect real-world judgments, drawing attention to a trainee's readiness for independent practice rather than his/her deficiencies. These scales fit into milestone measurement both by allowing an individual resident to strive for independence in entrustable professional activities across the entire training period and by allowing residency directors to identify residents experiencing difficulty. Some WBA tools that have begun to use variations of entrustability scales show potential for allowing raters to produce valid judgments. This type of anchor scale should be brought into wider circulation.